2004
DOI: 10.2527/2004.82113128x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a quantitative trait locus for muscle hypertrophy from Belgian Texel sheep on carcass conformation and muscularity

Abstract: A QTL for muscle hypertrophy has been identified in the Belgian Texel breed. A population of F2 and backcross lambs created from crosses of Belgian Texel rams with Romanov ewes was studied. Effects on carcass traits and muscle development of the Belgian Texel breed polygenes and Belgian Texel single QTL were compared. In both cases, carcass conformation and muscularity were improved. The Texel polygenic environment improved conformation mainly through changes in skeletal frame shape. Segments were shorter and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
39
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 11 publications
(11 reference statements)
6
39
0
Order By: Relevance
“…Three additional regions (out of 5) with LOD scores smaller than genome-wide significance thresholds appeared to be colocalized with domestic sheep weight-related QTLs. In domestic sheep, these regions contain QTLs for body weight and muscularity (chromosome 2, Laville et al, 2004;Walling et al, 2004;Margawati et al, 2009), body weight and growth rate (chromosome 23, Margawati et al, 2006Margawati et al, , 2009Raadsma et al, 2009) and body weight, growth rate and muscle mass (chromosome 24, Campbell et al, 2003;Raadsma et al, 2009). Possible candidate genes in these regions (genes known to influence weight-related traits in sheep or other species) identified by Raadsma et al (2009) include myostatin, beta-3-adrenergic receptor, melanocortin 4 receptor, erythropoietin, elastin and fibrosin genes.…”
Section: Body Massmentioning
confidence: 99%
“…Three additional regions (out of 5) with LOD scores smaller than genome-wide significance thresholds appeared to be colocalized with domestic sheep weight-related QTLs. In domestic sheep, these regions contain QTLs for body weight and muscularity (chromosome 2, Laville et al, 2004;Walling et al, 2004;Margawati et al, 2009), body weight and growth rate (chromosome 23, Margawati et al, 2006Margawati et al, , 2009Raadsma et al, 2009) and body weight, growth rate and muscle mass (chromosome 24, Campbell et al, 2003;Raadsma et al, 2009). Possible candidate genes in these regions (genes known to influence weight-related traits in sheep or other species) identified by Raadsma et al (2009) include myostatin, beta-3-adrenergic receptor, melanocortin 4 receptor, erythropoietin, elastin and fibrosin genes.…”
Section: Body Massmentioning
confidence: 99%
“…Consumer preferences in domestic and international markets drive the industry to produce meat cuts that are larger and leaner (Banks, 2002;Hall, Kelf, Fogarty, & Murray, 2000;Laville, Bouix, Sayd, & Bibé, 2004). To achieve this goal, Australian lamb producers currently select for lean meat yield percentage indirectly via three existing Australian Sheep Breeding Values (ASBVs) for postweaning weight (PWWT), c-site fat depth (PFAT) and eye muscle depth (PEMD), which are used to select for improved growth, leanness and muscling respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Macfarlane et al (2009) studied the TM-QTL effects on hind leg muscle volume and hind leg muscle density and analyses revealed no significant difference between carrier and non-carrier lambs. This study did not find any significant effects of the LM-QTL on the hind leg muscle characteristics of width, depth and 2D muscularity measured by CT. Muscularity describes the shape of the muscle and it has been shown that deeper muscles appeal to consumers, as they prefer rounded rather than thin chops (Laville et al, 2004). LM-QTL carrier lambs showed no significant change in muscularity in both the leg and loin regions, as measured from 2D CT scans.…”
Section: Discussionmentioning
confidence: 99%
“…This can be achieved by -E-mail: amer.masri@sac.ac.uk incorporating this information into breeding programmes through marker-assisted selection (MAS) schemes (Dekkers and Hospital, 2002;Dekkers, 2004). To date, many genes and QTLs affecting the muscle growth, carcass composition and meat quality have been reported in farm animals, several of which are found in sheep (Cockett et al, 1994;Nicoll et al, 1998;Broad et al, 2000;Marcq et al, 2002;Laville et al, 2004;Walling et al, 2004;Clop et al, 2006;Kijas et al, 2007;Hadjipavlou et al, 2008). However, very few causative mutations underlying the variations associated with traits of economic importance in sheep have been successfully identified and validated (Cockett et al, 1994;Clop et al, 2006;Wilson et al, 2001).…”
Section: Introductionmentioning
confidence: 99%